MY TEACHERS: A VIEW FROM A DISTANCE OF TIME - Хороб, С. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the selection of articles the attempt is made to systematise the analytical judgements of Belarusian literary scholars on the scientific creative work by Ivan Ovksentiiovych Denysiuk (1924-2009) and to research theoretical-methodological grounds for studying specifics of the aesthetic reception of the drama as a genre of literature and a kind of art in the scientific creative work by Roman Teodorovych Hromiak (1937-2012). Speeches at scientific conferences, commemorating the outstanding Ukrainian scholars-philologists, tireless researchers of the Ukrainian national literature, folklore and literary criticism, formed a basis for the articles. It is proved that the literary scientific richness (historical-literary and theoretical-literary), declared by their heritage, will forever be preserved in the home science about the fictional word.